Analysis of the Qur’an Recitation Development Institution in Improving Qari and Qariah Training in Jambi Province - Fahrizal Nover; Mukhtar Mukhtar; Wahyudi Wahyudi (Universitas Muhammadiyah Enrekang, 2024)
This study investigates the role of the Quran Recitation Development Institution (LPTQ) in enhancing the quality of Qari and Qariah training in Jambi Province. The findings indicate that LPTQ plays a vital role in advancing Quranic recitation skills by providing structured training programs, mentorship initiatives, and competitive platforms. These initiatives focus on improving the technical proficiency of participants in tajwid, fasohah, and maqamat while also fostering mental preparation and character development. However, challenges such as limited resources, inadequate facilities, and lack of stakeholder coordination hinder the optimal development of Quranic reciters. This research employs a qualitative approach, utilizing interviews, observations, and document analysis to provide an in-depth understanding of LPTQ’s strategies, challenges, and their impact on participants. The results highlight the importance of enhancing training facilities, improving stakeholder collaboration, and integrating advanced teaching materials and technologies to better address evolving societal needs. This study contributes to the understanding of Quranic education and offers practical recommendations for improving the effectiveness of LPTQ programs.